Acceptability and Usability of a Wearable Activity Tracker and Application Among Inactive Adolescent Girls. Issue 1 (3rd June 2020) - Voskuil, Vicki R.; Stroup, Sarah; Leyden, Madeline
Objective: To evaluate the acceptability and usability of the Fitbit Flex 2 TM activity tracker and application (app) among inactive adolescent girls. Design, Sample, and Setting: This mixed-methods study included girls in the 8 th and 9 th grades ( N = 33) recruited from a high school in the Midwest. Participants were given the Fitbit Flex 2 TM to wear for one week with access to the app. Measures: Daily steps, miles, and active minutes were measured. Girls participated in a focus group and completed a survey regarding acceptability and usability of the tracker and app. Results: Girls (14.62 ± 0.60 years) completed a daily average of 7, 758.87 ( SD = 1763.69) steps, 3.66 ( SD = 1.98) miles, and 21.69 ( SD = 13.71) minutes of moderate to vigorous physical activity (MVPA). Survey responses (scale of 0–3) indicated girls liked using the Fitbit ( Mean = 2.94, SD = .25) and reported it was easy to use ( Mean = 2.56, SD = .50). For girls who chose to use the app ( n = 28), all but one reported that they liked it. Girls reported the tracker increased their awareness of activity, helped them set goals, and motivated them to do more steps. Some girls reported issues with usability including difficulty getting the tracker on and off the wrist and confusion regarding the green light system. Conclusion: The Fitbit and app were well received by the inactive adolescent girls. A more advanced tracker with a screen display and improved reliability for capturing MVPA is suggested for future research.